Qur’anic Literacy Through Tadabbur Al-Qur’an Comic - Hidayatullah Ismail; Nasrul Fatah; Salman Salman; Muhammad Hafiz Saleh (Universitas Islam Negeri (UIN) Sultan Thaha Saifuddin Jambi, 2026)
Non-Indexed Publication